The Impact of the Extreme Air Temperatures on the Characteristics of Iraq Weather - Ahmed, Ehab Sh; Hassan, Ahmed S. (Iraqi Journal of Science, 2018)
Air Temperature is mainly affect the condition of temporal and spatial weather. This influence may be very high on some weather variables such as pressure, humidity and winds, also the Extreme of these variables can be considered as an indicator of the impact and intensity of the pressure systems. The data of the European Centre for Medium-Range Weather Forecasts (ECMWF) during the summer months (June, July and August) of the period (2006 - 2017) were used to extract the Extreme ​​of Daily Maximum Temperatures (EDMT) for four stations in Iraq (Baghdad, Basra, Khanaqin and AL-Rutba). The results that the number of extreme cases characteristics is nine, one of which is the beginning of the season, and the other was the end of the summer season and this confirms the stretch of the summer about a month May and September. This was done by considering 50°C/323°K as the most extreme values of two stations, and finding other extreme values for each region based on the maximum Temperatures anomalies. However, we must mention the geographical impact of (EDMT) and thus on the changing trajectory of the recipes of pressure pattern.